Augusto de campos e mondrian: um diálogo intersemiótico - Vasconcelos, Raíra Costa Maia de (2016)
This work aims at establishing dialogues between Augusto de Campos’ poetry and Piet Mondrian’s painting. Grounded in Russian School of Semiotics, we will show the poetic journey of the first one and the creative trajectory of the second one, in order to highlight some aesthetic convergence between them. The peculiarities of each artist and each of their studied works will be described based on Semiotics studies mentioned above. So, understanding the culture as aggregator tissue of symbolic systems is essential for the construction of our analysis, since it supports the arguments that aim at converging together two artists distant in time and space. Brazilian poetry and European painting will be presented in the chapter of analysis through four sections that already highlight evidences of dialogue in their works. The modern deconstruction view of the text and of the vanguard vitality will be perceived as confluent points and strong tension issues in each section of this investigation. Observing the poetic work in painting and the pictorial behavior in poetry directs the paths we pursue in this study